Left Behind by Design: Proficiency Counts and Test-Based Accountability - Neal, Derek; Schanzenbach, Diane Whitmore (The Review of Economics and Statistics, 2010)
We show that within the Chicago Public Schools, both the introduction of NCLB in 2002 and the introduction of similar district-level reforms in 1996 generated noteworthy increases in reading and math scores among students in the middle of the achievement distribution but not among the least academically advantaged students. The stringency of proficiency requirements varied among the programs implemented for different grades in different years, and our results suggest that changes in proficiency requirements induce teachers to shift more attention to students who are near the current proficiency standard.